Evaluation of the effect of non-surgical periodontal treatment on oral health impact profile in patients with periodontal diseases - Iessa, Mustafa Sayed (My University, 2020)
Amaç: Bu çalışmanın amacı, periodontal hastalığı olan hastalarda cerrahi olmayan periodontal tedavinin (C.O.P.T.) ağız sağlığı etki profili (O.H.I.P.-14 TR) üzerindeki etkisini değerlendirmektir.Gereç ve Yöntem: Periodontal durumlarına göre 3 gruba ayrılmış; periodontitis (n=30), gingivitis ve periodontal olarak sağlıklı (n=30), toplam 90 hasta çalışmaya dahil edildi. Plak indeks (P.İ.), gingival indeks, sondalamada kanama, sondalama derinliği, klinik ataşman seviyesini (K.A.S.) içeren peridodontal ölçümler ve O.H.I.P.-14 TR anketi C.O.P.T. önce ve sonra 1 ve 3 aylarda yapıldı. Bulgular: Bütün klinik parametreler ve O.H.I.P.-14 TR total skoru başlangıçta sağlıklı grupta anlamlı olarak daha düşük bulundu (p<0,05). Gingivitisli ve peridodontitisli grupta tüm klinik parametrelerde, O.H.I.P.-14 TR skorunda ve 7 alt gurubun skorunda C.O.P.T. sonrası anlamlı azalma olduğu, grup içi ve gruplar arası karşılaştırmada anlamlı fark bulunduğu tespit edildi (p<0,05). Periodontitis grubunun O.H.I.P.-14 TR skoru ile P.İ. ve K.A.S. arasında 3. ayda düşük bir ilişki olduğu bulundu (p<0,05).Sonuç: Çalışmanın sınırları dahilinde, bu çalışma, C.O.P.T.’nin O.H.I.P.-14 TR skorlarını düşürdüğü, gingivitis ve periodontitisli gurupta ağız sağlığı ile ilişkili yaşam kalitesini pozitif olarak etkilediğini göstermektedir

Aim: The aim of this study was to evaluate the effect of non-surgical periodontal treatment (N.S.P.T.) on the oral health impact profile-14 TR (O.H.I.P.-14 TR) in patients with periodontal disease.Material and Method: A total of 90 patients, diagnosed with periodontitis (n=30), gingivitis (n=30) and periodontally healthy (n=30) according to their periodontal status, were included. Plaque index, gingival index, bleeding on probing, probing depth, clinical attachment level, periodontal clinical measurements and the O.H.I.P.-14 TR questionnaire were measured and performed at baseline, 1 and 3 months after N.S.P.T.Results: At baseline, all clinical parameters and O.H.I.P.-14 TR score were significantly low in the healthy group (p<0,05). The periodontal clinical parameters, the total O.H.I.P.-14 TR scores and the scores in all 7 domains significantly decreased after N.S.P.T. in the gingivitis and peridontitis groups, and a significant difference between the gingivitis and periodontitis at baseline and follow-up periods was observed (p<0,05). There was a low correlation between the O.H.I.P.-14 score of group P for P.I. and C.A.L at 3 month (p<0,05).Conclusion: Within the limits of this study, it was observed that N.S.P.T. reduced O.H.I.P.-14 TR scores and had a positive effect on patients’ oral health related quality of life both in groups G and P.
Keywords: cerrahi olmayan periodontal tedavi; Dentistry; Diş Hekimliği; Gingivitis; gingivivtis; Health; health related quality of life; non-surgical periodontal debridement; periodontitis; quality of life; Sağlık; Sağlık ile ilişkili yaşam kalitesi; yaşam kalitesi